COVID-19 vaccine for adolescents with chronic disease or disabilities - Tjahjono, Harjoedi Adji; Almiradani, Ayunda; Salim, Irfan Agus; Mutaqi, Fadilah; Ariani; Wulandari, Hajeng (Medical Faculty of Brawijaya University, Indonesia, 2023)
Background: Indonesia has a relatively high number of COVID-19 cases and mortalities, including children and adolescents groups. Vaccination coverage for these groups is currently low, especially in the population of children with disabilities and special needs, due to the difficulty of assisting them. The objective of this study was to share the data on the COVID-19 vaccine for adolescents with chronic diseases or disabilities. Methods: This descriptive study uses data collected from two hospitals in September 2021. We analyzed the patients' characteristics, age groups, diagnoses, comorbidities, and adverse events following immunization (AEFI) of the adolescents injected with the COVID-19 vaccine. Results: From a total of 94 adolescents, 51 have disabilities, and 43 have chronic disease. Disabilities include children with special needs (54%), attention deficit and hyperactivity disorder (4%), autism (11%), cerebral palsy (4%), and Down syndrome (27%). The accompanying chronic diseases vary widely, such as diabetes mellitus (28%), asthma (14%), rheumatic heart disease (14%) and thalassemia (14%). There were 6 patients found to have AEFI. Three of them have diabetes mellitus, the other two patients have thalassemia, and the other one patient has Down syndrome. Varies AEFIs were found, including fever, drowsiness, weakness, dizziness, hunger, and itching. All symptoms were improved within hours and did not require hospitalization. Conclusion: Adolescents with disabilities and chronic diseases require special assistance and extra care during vaccination. The COVID-19 vaccine is relatively safe for adolescents in these groups without significant side effects.